2020
DOI: 10.1111/jpn.13316
|View full text |Cite
|
Sign up to set email alerts
|

Influence of allicin administration on reproductive efficiency, immunity and lipid peroxidation of rabbit does under high ambient temperature

Abstract: This study investigated the effect of daily oral administration with allicin levels (0, 5 and 10 mg/kg of female body weight), 30 days pre‐insemination, on reproductive performance in vivo and in vitro, immunity, and oxidative stress of rabbit does under high ambient temperature. Niliparous NZW does (n = 105) were randomly divided into three groups (35 in each) treated with 0, 5 and 10 mg allicin dissolved in 2 ml distilled water, respectively, for 30 days pre‐insemination. At the end of treatment (30 days), d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
3
15
1
Order By: Relevance
“…In the current study, supplementation of TEO to male rabbits signi cantly decreased serum urea, creatinine, ALT and AST activity, as well as increased serum testosterone levels compared to PC and NC groups. These results are in accordance with those of El-Ratel et al [ 13] reported that the activity of AST and ALT of rabbits were signi cantly improved by oral administration of phytogenic (5 or 10 mg allicin/ BW) compared with the control. Supplementation of 2.5% of thyme leaves to rabbit diets signi cantly decreased urea and creatinine [ 14].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, supplementation of TEO to male rabbits signi cantly decreased serum urea, creatinine, ALT and AST activity, as well as increased serum testosterone levels compared to PC and NC groups. These results are in accordance with those of El-Ratel et al [ 13] reported that the activity of AST and ALT of rabbits were signi cantly improved by oral administration of phytogenic (5 or 10 mg allicin/ BW) compared with the control. Supplementation of 2.5% of thyme leaves to rabbit diets signi cantly decreased urea and creatinine [ 14].…”
Section: Discussionsupporting
confidence: 92%
“…El-Ratel et al [ 13] reported that oral administration of phytobiotic improved liver function of rabbits compared with the control. Likewise, supplementation of 2.5% of thyme leaves to rabbit diets signi cantly improved kidney function by decreased urea and creatinine levels [ 14].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, supplementation of TEO to male rabbits significantly reduced serum urea, creatinine, and ALT and AST activities and increased serum testosterone levels compared to PC and NC groups, but the values were within the normal physiological range [14,16,[29][30][31]. These results agree with those of El-Ratel et al [14], where it is reported that the activity of AST and ALT of rabbits was remarkably enhanced by oral administration of phytogenic additives (5 or 10 mg allicin/BW) compared to the control. Supplementation of 2.5% of thyme leaves to rabbit diets significantly decreased urea and creatinine [15].…”
Section: Discussioncontrasting
confidence: 45%
“…In the current study, supplementation of TEO to male rabbits significantly reduced serum urea, creatinine, and ALT and AST activities and increased serum testosterone levels compared to PC and NC groups, but the values were within the normal physiological range [ 14 , 16 , 29 , 30 , 31 ]. These results agree with those of El-Ratel et al [ 14 ], where it is reported that the activity of AST and ALT of rabbits was remarkably enhanced by oral administration of phytogenic additives (5 or 10 mg allicin/BW) compared to the control. Supplementation of 2.5% of thyme leaves to rabbit diets significantly decreased urea and creatinine [ 15 ].…”
Section: Discussionmentioning
confidence: 67%
“…These active components had the best oxidative status [ 12 ] and may reduce serum cholesterol [ 13 ], which could improve the reproductive performance of rabbits. El-Ratel et al [ 14 ] reported that oral administration of phytobiotics improved the liver function of rabbits compared to the control. Similarly, supplementation of 2.5% of thyme leaves to rabbit diets remarkably enhanced kidney function by decreasing urea and creatinine levels [ 15 ].…”
Section: Introductionmentioning
confidence: 99%